Designing effective discussion forum in MOOCs: insights from learner perspectives - Neha,; Kim, Eunyoung (Frontiers in Education, 2023)
Introduction The study focuses on addressing the gap between the perspectives of learners and the designers of Massive Open Online Courses (MOOCs), with a particular emphasis on asynchronous discussion forums within these courses. The primary objective of this study is to bridge the gap in understanding between MOOC designers and learners regarding the organization and usability of discussion forums. Methods It aims to achieve this objective through a navigation experiment that investigates three main factors: (1) Classification of Discussion Forum Posts: This involves how discussion forum posts are categorized or organized. (2) Design of Different Discussion Forum Patterns: The study explores the effectiveness of various discussion forum design patterns. (3) Evaluation of Learners’ Perspective: It assesses the learners’ experiences and viewpoints regarding the discussion forums. The study identifies a gap in prior research, where the learner’s perspective has often been neglected when examining discussion forum organization and usability in MOOCs. Results The results of the study indicate that the redesigned discussion forum was successful in reducing the time required by learners to navigate and explore the discussion forum. This suggests that improvements in interactive user interfaces, design elements, usability, and time efficiency can enhance the design of asynchronous discussion forums in MOOCs. The study offers recommendations and insights that MOOC designers can implement to create more effective and engaging discussion forums. These recommendations are based on the identified features and design elements that are crucial for learner satisfaction and interaction efficiency. Implementing the study’s findings by considering learner perspectives, MOOC designers can enhance the overall quality of the learning process. This includes making the learning environment more engaging for both learners and instructors. Discussion The study contributes to the field of online education by emphasizing the importance of learner perspectives and offering practical guidance on optimizing the design, usability, and time efficiency of discussion forums in MOOCs. In summary, this study seeks to improve the design of asynchronous discussion forums in MOOCs by focusing on the learners’ perspective, usability, and efficiency. It not only identifies key factors but also provides recommendations for MOOC designers to enhance the learning experience and engagement within these online courses.